2014
DOI: 10.1353/hsj.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Creation of Caring Student-Teacher Relationships: Does Teacher Understanding Matter?

Abstract: This study explores the role of high school students’ perceptions of teacher understanding in the development of caring student-teacher relationships. Whereas past research has embedded understanding as a facet of care, this research distinguishes between care and understanding to examine whether and how understanding is necessary for care. Extending Noddings’ (1992) conceptions of caring as virtue and caring as relation to consider understanding as virtue and understanding as relation , the researchers analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…In contrast to some prior research (Cooper and Miness, 2014;Tosolt, 2010), caring was not exclusively seen as an individual faculty member's personality trait but also as a practice evidenced through teaching techniques employed. Students identified two specific areas in which caring was seen (or not) in their interactions with faculty -faculty attitude or demeanor and pedagogical practices in class.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast to some prior research (Cooper and Miness, 2014;Tosolt, 2010), caring was not exclusively seen as an individual faculty member's personality trait but also as a practice evidenced through teaching techniques employed. Students identified two specific areas in which caring was seen (or not) in their interactions with faculty -faculty attitude or demeanor and pedagogical practices in class.…”
Section: Resultsmentioning
confidence: 76%
“…The importance of teachers' caring about students has been well established, although virtually all of the existing research has focused on secondary schools rather than the higher education context (Dallavis, 2014;Meyers, 2009;Noblit, Rogers, and McCadden, 1995;Teven 2007;Teven and Hanson, 2004). In studies of teacher efficacy and student responsiveness, perceived caring consistently emerges as a significant variable shaping student engagement, teacher credibility, and student performance in these settings (Cooper and Miness, 2014;Finn et al, 2009). Frequent interactions with students, assistance with personal and academic challenges, fairness in classroom treatment, listening and encouraging students, smiling and being "warm," and efforts to learn about students' lives have all been associated with seeing a teacher as caring (Cooper and Miness, 2014;Tosolt, 2010).…”
Section: Teaching Caring and Student Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Education researchers have established a strong positive correlation between teacher caring and improved student retention and academic success [3][4][5][6][7][8][9][10][11]. In the literature, and in my own operationalization, teacher caring includes getting to know students personally, providing them socio-emotional support, fostering a sense of belonging, attending to students' physiological needs, and cultivating a sense of mutuality, connection, and desire to understand and help each other [3,4,10,[12][13][14][15][16][17][18].…”
Section: Care Poor Students Of Color and Cultural Capital: A Reviewmentioning
confidence: 99%
“…These and other teacher characteristics and behaviors (i.e., respect for, interest in, and fair treatment of students, Matsumura et al, 2008; teachers being nonjudgmental, Kennedy, 2011) have been conceptualized in the literature as teacher (affective) support (Anderman, Andrzejewski, & Allen, 2011;Sakiz, Pape, & Hoy, 2012) or teacher care (Perry, Liu, & Pabian, 2010;Tosolt, 2009) and understanding (Cooper & Miness, 2014). For example, den Brok, Fisher, and Koul (2005) conducted a study of teacherstudent interpersonal behavior and students' attitudes toward science and found that teacher interpersonal behavior explains more than 12% of the total variance in students' attitudes toward science.…”
Section: Student-teacher Interactionsmentioning
confidence: 99%